1999
DOI: 10.1253/jcj.63.315
|View full text |Cite
|
Sign up to set email alerts
|

A Case in Which Stent Insertion is Considered to Have Triggered Contrast Medium-Induced Coronary Vasospasm

Abstract: he use of contrast medium has recently increased in various fields, including coronary angiography, but reports of induction of spasm in the coronary artery caused by contrast media are rare. [1][2][3][4][5][6] In the case reported here, a stent was placed for restenosis after percutaneous transluminal coronary angioplasty (PTCA) in a patient with no history of coronary vasospastic angina pectoris, but spasm appeared to be induced by the contrast medium Iomeprol. Case ReportA 75-year-old man was admitted to ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Interestingly, the incidence of hypotension was not significantly different than in the historic control group (fenoldopam = 3.8% vs control = 1.7%, P = ns ). Coronary interventions in this study included stent, Rotablator, Rota + stent, and AngioJet + stent, all of which are well known in carrying the risk of bradycardia and hypotension 35–41 . This study clearly documented the prophylactic effect of fenoldopam against radiocontrast‐induced nephropathy in patients with kidney disease both with and without diabetes.…”
Section: Fenoldopam and Radiocontrast‐induced Nephropathymentioning
confidence: 68%
See 3 more Smart Citations
“…Interestingly, the incidence of hypotension was not significantly different than in the historic control group (fenoldopam = 3.8% vs control = 1.7%, P = ns ). Coronary interventions in this study included stent, Rotablator, Rota + stent, and AngioJet + stent, all of which are well known in carrying the risk of bradycardia and hypotension 35–41 . This study clearly documented the prophylactic effect of fenoldopam against radiocontrast‐induced nephropathy in patients with kidney disease both with and without diabetes.…”
Section: Fenoldopam and Radiocontrast‐induced Nephropathymentioning
confidence: 68%
“…Coronary interventions in this study included stent, Rotablator, Rota + stent, and AngioJet + stent, all of which are well known in carrying the risk of bradycardia and hypotension. [35][36][37][38][39][40][41] This study clearly documented the prophylactic effect of fenoldopam against radiocontrast-induced nephropathy in patients with kidney disease both with and without diabetes. Regretfully, the lack of randomization precludes definitive conclusion of fenoldopam's protective role against RIN.…”
Section: Fenoldopam and Radiocontrast-induced Nephropathymentioning
confidence: 73%
See 2 more Smart Citations
“…1,2) In addition several studies have reported that stent implantation is an option for the treatment of coronary vasospastic angina (VSA) that is resistant to adequate medical treatment. [3][4][5][6][7][8][9] On the other hand, Muroya, et al 10) reported that stent implantation can induce severe stent-edge spasm in patients without coronary spasm before stent implantation. In this situation, the following questions arise.…”
mentioning
confidence: 99%